METHODOLOGICAL ASPECTS OF USING CHILDREN'S LITERATURE OF THE INDEPENDENCE PERIOD IN CLASSROOM LESSONS IN PRIMARY GRADES - Otanazarova Mohirahon Hamidbekovna (American Journals, 2023)
This article provides information on the formation of children's literature, children's literature of the period of independence, and methodical aspects of using children's literature of the period of independence in extracurricular reading classes in elementary grades.
Keywords: young generation, children, literature, education, science, enlightenment, writer, prose.